117k views
3 votes
Multiply (9x+2y)(9x-2y)

User Auzy
by
4.8k points

2 Answers

5 votes

Answer- 81x² - 4y²

All the steps listed below

(9x + 2y) × (9x - 2y)

9x × 9x = 81x²

9x × -2y = -18xy

2y × 9x = 18xy

2y × -2y = -4y²

81x² - 18xy + 18xy - 4y²

-18xy + 18xy = 0


User Marcus Hughes
by
5.2k points
4 votes

Hi there!

Here are all the steps into multiplying these 2 parentheses :

(9x + 2y) × (9x - 2y)

9x × 9x = 81x²

9x × -2y = -18xy

2y × 9x = 18xy

2y × -2y = -4y²


81x² - 18xy + 18xy - 4y²


-18xy + 18xy = 0


Your answer is: 81x² - 4y²


There you go! I really hope this helped, if there's anything just let me know! :)

User Vadim Yelagin
by
5.4k points